Acute effect of vibratory stimulation on elbow joint flexor performance - Tu, J. W.; Lin, C. T.; Wu, J. J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
A novel design of vibratory stimulation training system was developed in this study. Each participant took a pre-test, before receiving treatment with 20 seconds of vibratory stimulation (VS) at a specific frequency and amplitude. The participants then took a post-test. Percentage improvement was then calculated by comparing the pre- and post-test values for each index. The experimental data were analyzed through a two-way repeated-measures ANOVA analysis, with the independent variables being vibratory frequency and amplitude and the dependent variables being EMG root mean square, maximal force, rate of force development, and average force. The optimal vibratory stimulation pattern was found from this study that being a 60% maximal force loading combined with VS at 2.5 Hz and 1 N amplitude sustained over 20 s.